Efficacy of fibrinogen concentrate in major abdominal surgery – A prospective, randomized, controlled study in cytoreductive surgery for pseudomyxoma peritonei. (26th November 2019) - Roy, Ashok; Stanford, Sophia; Nunn, Sean; Alves, Sue; Sargant, Nigel; Rangarajan, Savita; Smith, Emily Arbuthnot; Bell, John; Dayal, Sanjeev; Cecil, Tom; Tzivanakis, Alexios; Kruzhkova, Irina; et al.
Abstract: Background: Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy for pseudomyxoma peritonei (PMP) is associated with excessive bleeding and acquired fibrinogen deficiency. Maintaining plasma fibrinogen may support hemostasis. Objectives: To compare hemostatic efficacy and safety of human fibrinogen concentrate (HFC) vs cryoprecipitate as fibrinogen sources for bleeding patients with acquired fibrinogen deficiency undergoing PMP CRS. Methods: FORMA‐05 was an off‐label single‐center, prospective, randomized, controlled phase 2 study. Patients undergoing PMP surgery with predicted intraoperative blood loss ≥2 L received human fibrinogen concentrate (HFC; 4 g) or cryoprecipitate (two pools of 5 units, containing approximately 4.0‐4.6 g fibrinogen), repeated as needed. The primary endpoint was a composite of intraoperative and postoperative efficacy, graded using objective 4‐point scales and adjudicated by an independent committee. Results: One hundred percent of patients receiving HFC (95% confidence interval: 83.9‐100.0, n = 21) or cryoprecipitate (84.6‐100.0, n = 22) achieved hemostatic success. HFC demonstrated noninferior efficacy ( P  = .0095; post hoc) and arrived in the operating room 46 minutes faster. There were significantly greater mean increases with HFC vs cryoprecipitate in plasma fibrinogen (0.78 vs 0.35 g/L; P  < .0001) and FIBTEM A20 (3.33 vs 0.93 mm; P  = .003). Factor XIII, factor VIII, and von Willebrand factor activity were maintained throughout surgery. Only red blood cells were transfused intraoperatively (median units: HFC group, 1.0; cryoprecipitate group, 0.5). Thromboembolic events were detected with cryoprecipitate only. Safety was otherwise comparable between groups. Conclusions: Human fibrinogen concentrate was hemostatically efficacious in patients undergoing major abdominal PMP surgery, with a favorable safety profile. These results are relevant to other surgical settings where bleeding and acquired fibrinogen deficiency occur.